The use off perioguide in surgery to correct gingival smile (Research, Society and Development, 2022)
The aesthetic standard requires beautiful and harmonious smiles, which encourages the search for dental procedures to correct imperfections in the stomatognathic system. In periodontics, plastic surgeries with the aim of correcting the so-called gummy smile are becoming progressively routine. With the advent of new technologies, aesthetic treatment options increase, becoming less invasive, less traumatic and with greater predictability, enabling emphasis in this area. In this sense, the perioguide is taken as an object of research, since its purpose is to help dentists in predicting gummy smile correction surgery. This work is a single case study, as it intends to report a work dealing with gingivoplasty/gingivectomy surgery using the perioguide. The interdisciplinary work between the specialties of Periodontics was concluded, with Radiology aided by technology, which enables the improvement and optimization of gingivoplasty/gingivectomy surgery. The use of the perioguide was a differential for treatment success.